2015
DOI: 10.1245/s10434-015-4430-6
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Multifocal and Multicentric Breast Cancers

Abstract: MF and MC tumors seem to be biologically different diseases. MC is clinicopathologically more aggressive than MF disease and is more frequently associated with younger age and larger tumor size and also is an independent predictor of node positivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 29 publications
2
45
0
Order By: Relevance
“…Previous work has demonstrated that women with a history of ADH or ALH are at increased risk for developing breast cancer . However, to our knowledge, no study has reported on the risk of MFBC with respect to a prior history of PBDA . Our results demonstrate that in a cohort of women with breast cancer, those with a history of PBDA are more likely to present with MFBC than women with no history of PBDA.…”
Section: Discussionsupporting
confidence: 45%
See 4 more Smart Citations
“…Previous work has demonstrated that women with a history of ADH or ALH are at increased risk for developing breast cancer . However, to our knowledge, no study has reported on the risk of MFBC with respect to a prior history of PBDA . Our results demonstrate that in a cohort of women with breast cancer, those with a history of PBDA are more likely to present with MFBC than women with no history of PBDA.…”
Section: Discussionsupporting
confidence: 45%
“…Our study was underpowered to detect an association between LCIS and MFBC (OR, 2.81; 95% CI, 0.52‐14.92) . The study contained only 15 women with a prior diagnosis of LCIS, and 2 of these women were confirmed to have MFBC.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations